Analysis of spatial coherence length of high harmonic generated in argon - Abdul Aziz, Nor Azah; Mohd Tarmizi, Emma Ziezie; Khuong, Ba Dinh (Springer, 2021)
High harmonic generation is a table-top laboratory-sized facility has emerged as another potential for extreme ultraviolet/X-ray coherent source in high-resolution microscopy and imaging applications. Previous research on coherence study in HHG has relied primarily on fringe visibility to characterize spatial coherence. To our knowledge, no studies have been done to calculate spatial coherence length of a high harmonic generation source. To determine the extent to which the source remain coherent, we investigated the spatial coherence properties by means of Young’s double slit experiment using slit separation from 20 to 150 μm in order to obtain interference data. An analytical method is used to estimate fringe visibility eventually be used to characterize coherence properties of each harmonic. In this work, high harmonic generation is produced in gaseous medium driven by intense laser pulses. Contrary to the assumption that coherence length may depend on harmonic intensity, however, our findings show that the spatial coherent length of the HHG source does not depend on harmonic intensity, but decreases with harmonic order, with a significant decrease in harmonics near the cut-off. This feature resembles the shape of the harmonic spectrum of a single atom.